1998
DOI: 10.1074/jbc.273.12.6982
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl-terminal 90 Residues of Porcine Submaxillary Mucin Are Sufficient for Forming Disulfide-bonded Dimers

Abstract: COS-7 cells transfected with expression vectors encoding 90 and 154 amino acid residues, respectively, from the carboxyl terminus of the disulfide-rich domain (240 residues) of porcine submaxillary mucin were shown to form disulfide-bonded dimers. Cells with expression vectors that encoded the disulfide-rich domain lacking the last 90 and 150 carboxyl-terminal residues, respectively, from the carboxyl terminus of the disulfide-rich domain were unable to secrete truncated domains. These results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 25 publications
1
48
1
Order By: Relevance
“…TGFβ2 dimerizes via a cysteine residue located directly at the N-terminus of the fourth cysteine residue in the cystine-knot motif [14]. Perez-Vilar and Hill [16] have performed a thorough mutagenesis study of the cysteine residues in the C-terminus of PSM and analysed these constructs in transfected COS-7 cells. Although they show a relatively high background 'activity' in the stacking/separation gel interface, they found three cysteine residues in the cystineknot motif that were likely to be involved in the dimer formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFβ2 dimerizes via a cysteine residue located directly at the N-terminus of the fourth cysteine residue in the cystine-knot motif [14]. Perez-Vilar and Hill [16] have performed a thorough mutagenesis study of the cysteine residues in the C-terminus of PSM and analysed these constructs in transfected COS-7 cells. Although they show a relatively high background 'activity' in the stacking/separation gel interface, they found three cysteine residues in the cystineknot motif that were likely to be involved in the dimer formation.…”
Section: Discussionmentioning
confidence: 99%
“…This proposes that this cysteine might be involved also in the dimerization of mucins. Studies on rat Muc2 [11,12] point out that this cysteine residue is essential for dimer formation, whereas studies on vWF [15], PSM [16] and Norrin [17] indicate that additional cysteine residues may be of importance. The mucin genes MUC2, MUC5AC, MUC5B and MUC6 are clustered on chromosome 11p15.5 [18], all of which contain the cystine-knot motif and show large similarities in the positions of other cysteine residues also outside of the cystine-knot motif, indicating that these mucin genes are part of a family having a common ancestral gene.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on PSM have shown that this mucin forms C-to-C dimers in the endoplasmic reticulum (12,13) followed by N-to-N multimerization through the D-domains in the distal part of the Golgi (10). CGLCG sequences in the D1 and D3 domains have been suggested to be crucial for N-to-N multimerization, and these sequences are highly conserved in other secreted mucins, including MUC5B.…”
Section: Figmentioning
confidence: 99%
“…The human oligomeric mucins have been postulated to be assembled in a manner similar to the vWF (6), and PSM has been shown to form C-to-C dimers in the endoplasmic reticulum (12,13) followed by N-to-N multimerization through the D-domains in the distal part of the Golgi (10). PSM shows homologies to MUC5B, MUC2, and vWF, including the D1, D2, and D3 domains, and it has been suggested that half-cysteine residues in the D1 and D3 domains are needed for multimerization of this mucin (10).…”
mentioning
confidence: 99%
“…The CK domain, which includes 85±90 residues near the C-terminal end, has been shown to be important in mediating dimerization of vWF and porcine submandibular mucin [9]. Immediately C-terminal to the CK domain in human intestinal MUC2 and rat Muc2 there is a unique 14-amino-acid cationic domain, which completes the polypeptide chain.…”
mentioning
confidence: 99%